(untitled) (Fiep Bulletin - online, 2010)
In this brief bibliographic revision, the author writes about how the Capoeira teacher should act once working in formal educational institutions, especially in the first scholar years – primary school (3 to 6 years old). Issues related to this are raised, such as the Capoeira development process in the formal education, the children’s psycho-social, psycho-motor, and affective development, and the Capoeira role in this whole process; the way Capoeira should be conducted once inserted in the school, and the relationship between the education, psychomotricity, and Capoeira. The author understands that Capoeira teachers that works in the formal education, especially in the first scholar years, should act as facilitators in the total children’s development, always respecting their natural development process, using Capoeira as a powerful tool, but not seeing it as the final objective of the work - end. Therefore, the author sees as crucial and fundamental the teacher preparation, his/her understanding about the concepts of school Capoeira, its educational process, and how it can contribute to this process, always aiming, over all, the development of bio-physical, bio-social, and bio-psychic parameters of the children.